Photocatalytic Deactivation of E. coli Bacteria by Copper(II) Oxide Doped-Titanium Dioxide Nanocomposite in Water Catchment Systems - Kustomo, Kustomo; Wu, Xiaoli (Universitas Gadjah Mada, 2025)
This study investigates the synthesis and evaluation of CuO-doped TiO2 nanocomposites for photocatalytic deactivation of Escherichia coli in the water catchment systems. Nanocomposites with varying CuO concentrations (0.25, 0.50, and 0.85% w/w) doped into TiO2 were prepared via the co-precipitation method and characterized by FTIR, SEM-EDS, and UV-vis DRS. The incorporation of CuO into TiO2 resulted in a progressive reduction of band gap energy, with the 0.85% CuO-TiO2 sample exhibiting the lowest value. Photocatalytic testing demonstrated that the 0.85% CuO-TiO2 nanocomposite achieved a 99.23% reduction of E. coli, surpassing the performance of undoped TiO2. The enhanced activity is attributed to improved visible light absorption and more efficient charge separation due to the synergistic effect between CuO and TiO2. These results indicate that optimizing CuO doping in TiO2 nanocomposites can significantly enhance photocatalytic disinfection, offering a promising solution for water treatment applications.